Ecological politics : ecofeminists and the Greens - Gaard, Greta Claire (Temple University Press, 1998)
An illuminating account of two interconnected social movements from their grassroots origins in the 1970s to the 1996 Green presidential campaign.
Keywords: Green movement -- United States.; Ecofeminism -- United States.; Environmental policy -- United States.; Environmental ethics -- United States.; Écologisme -- États-Unis.; Écoféminisme -- États-Unis.; Environnement -- Politique gouvernementale -- États-Unis.; Éthique de l'environnement -- États-Unis.; SCIENCE -- Environmental Science (see also Chemistry -- Environmental); POLITICAL SCIENCE -- Public Policy -- Environmental Policy.; SOCIAL SCIENCE -- Women's Studies.; Ecofeminism; Environmental ethics; Environmental policy; Green movement; United States; Ökologische Bewegung; Feminismus; USA